Necesidad social de la regulación emocional en estudiantes al iniciar la práctica estomatológica/Social need for emotional regulation in students at the beginning of dental practice - Norys Tan Suárez; Mayelin Soler Herrera; Soledad Yanedy García Peláez (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
The results of a bibliographic review carried out from May to July 2021 are presented; as part of the research related to the formation of emotional regulation competence in Dentistry students at the beginning of clinical practice. To carry out this work, theoretical methods such as historical-logical, analysis-synthesis and induction-deduction were used, with the aim of explaining, from a Science, Technology and Society approach, the need for the formation of this competence in care performance. The main results are that society needs dentistry graduates to have scientific-technical skills in accordance with their professional profile, but also, demands an expert who offers confidence. Through the emotional regulation competence, students have the ability to react appropriately to their personal emotions and those experienced by patients. It is concluded that the education and training processes must take into account the development of emotional competencies by integrating them into the curriculum.